Social and passionate factors of a Wayuu native and their impact on learning Spanish - Carrillo García, Stefany (Rastros Rostros, 2015)
Introduction: this article is part of the research line “Educational Practices” of the research group Colombian Culture and Fiction (cuynaco). Its aim is to determine how social and emotional conflicts are expressed as reasons for wanting to speak Spanish as a second language in the discourse of a Wayuu native student.Methodology: the analysis adopts two perspectives: discourse semiotics proposed by Courtes and Greimas and passionate semiotics by Fontanille.Results: the study sets out how the different political practices and the State intervention, in relation to the social conflicts of indigenous ethnic groups, encourage a Wayuu student to appropriate the dominant language in Colombia (Spanish).Conclusions: in this manner, the need for college education is encouraged to defend the rights of this community.
Keywords: discourse analysis; Spanish as a second language; semiotics of passions; tensive semiotics